The Question Concerning Market Economy: Disturbing Crisis and Provocative Production (Culturas Científicas, 2021)
The present article aims to propose the question of economic technique in the Heideggerian sense of asking. By "Heideggerian sense" we refer to the way in which Heidegger proposes the question of technique from the disturbance caused by modern technique. In other words, we ask about "the" economic technique inspired by the consequences – past, current, and potential – of modern economic technique: the market economy. The work will proceed as follows. First, we present the question of economic technique, explaining the reasons that lead us to it and the Heideggerian inspiration behind this question. In particular, we point to the phenomenon of the economic crisis in its contemporary sense. Second, we will seek to show that, as Heidegger did with technique, it is not possible to speak of "the" economy, but it will be necessary to distinguish between an ancient economy and a modern economy. Third, we will turn to the historical-anthropological study of Karl Polanyi to describe the distinction between these two ways of conceiving the economic. Fourth, from the previous description we will show that the market economy is not a mere instrument for the production of material conditions, as it is characterized by a provocative essence. Finally, we will conclude on the consequences and possibilities of this philosophical description of the market economy.
Keywords: Market economy; Martin Heidegger; Karl Polanyi; Philosophy of economics